Reduced shoulder strength and change in range of motion are risk factors for shoulder injury in water polo players. (November 2019) - Hams, Andrea; Evans, Kerrie; Adams, Roger; Waddington, Gordon; Witchalls, Jeremy
Abstract: Objective: To determine whether pre-season shoulder ROM and strength can be used to identify athletes at risk of future shoulder injury. Design: Prospective cohort. Setting: High performance sports institute. Participants: 76 sub-elite water polo players. Main outcome measures: Mean pre-season shoulder internal (IR) and external rotation (ER) ROM and strength values compared by gender, dominance and prospective injury status. Results: 14-dominant shoulder injuries were recorded. There was a significant difference (p = 0.05) in total ROM difference (TROM) between the prospectively injured and no injury groups (−17.2°(30.4);-0.8°(13.3)), and dominant side ER strength (11.7%(2.4) vs 14.5%(2.8), p = 0.03) and IR strength (16.5%(3.0) vs 21.6%(4.9) as a percentage body weight (PBW) were also significantly different (p ≤ 0.03). Separate significant associations were found between future episodes of shoulder injury and; dominant shoulder TROM difference of ≥7.5°(OR 3.6, 95%CI 0.8–16.0), ER strength as a PBW≤12.5%(OR 5.2, 95%CI 1.0–27.9), and IR strength as a PBW≤16.8%(OR 13.8, 95%CI 2.2–88.0). Conclusion: Pre-season dominant TROM difference, and reduced shoulder IR and ER strength relative to body weight were significant predictors for future shoulder injury. Although further investigation with a larger sample size is required, achieving optimal values on these measures may reduce future episodes of shoulder injury in water polo players. Highlights: Pre-season TROM difference of ≥7.5° was a significant predictor for future episodes of shoulder injury. Shoulder IR strength PBW of ≤16.8% was a significant predictor for future episodes of shoulder injury. Shoulder ER strength PBW of ≤12.5% was a significant predictor for future episodes of shoulder injury.